16 Managing scimitar syndrome: the birmingham perspective. (28th April 2017) - Kinsella, C; Bowater, S; Botha, P; Hudsmith, L; Thorne, S; Barron, D; Jones, T; Khan, N; Clift, P
Abstract : Aim: To evaluate the long-term outcomes of patients diagnosed with Scimitar syndrome in Birmingham from 1988–2016. Methods: Data was collected retrospectively using medical records. Scimitar syndrome was defined as a right hemi anomalous pulmonary venous connexion to the Inferior Vena Cava. Results: Twenty-nine patients diagnosed with Scimitar syndrome were identified. Three distinct subgroups emerged: the "Early Scimitars" (n=6), the "Stable Scimitars" (n=11) and the "Surgical Scimitars" (n=12). The Early Scimitars had a median age at diagnosis of 30 days. They all presented with severe respiratory distress and most had associated congenital defects (n=5). There was 100% mortality in this group. Stable Scimitars had a median age at diagnosis of 11 months. In this group, six patients (54.5%) were symptomatic. Coil embolisation of the collateral arterial supply to the right lung abolished symptoms in 50% of cases (n=3). Surgical Scimitars had a median age at diagnosis of 17.3 years; nine (75%) underwent surgical repair of their Scimitar vein. One was lost to follow up. Overall, four patients (50%) developed post-operative complications and two developed Scimitar vein stenosis (25%). There was one late post-operative death (13%). Conclusion: There is a high mortality in the Early Scimitars. Stable Scimitars may benefit from coil embolisation and should be conservatively followed up. Due to the significant risk of complications, surgical correction should be reserved for the symptomatic and those developing co-morbid disease (increasing right ventricular dilation, arrhythmia). If asymptomatic, surveillance in the form of MRI, cardiopulmonary exercise tolerance and echocardiography should be offered.